Terceirização e trabalhadores da construção civil na cidade de Araraquara/SP - Scavichia, Gloriete Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The transformations in work in the universe are affecting intensely to industrial societies around the world, so that the restructuring of productive activities, including technological innovations and new management of the workforce resulting in a significant increase in rates productivity, profound changes in the relationship between companies and ways of organizing production, interfering in labor relations and negotiations with the institutions that protect workers. This research aims to analyze the flexibility of labor relations, embodied in labor outsourcing process in the economic segment construction in Araraquara / SP. Therefore, we propose an initial analysis of the Fordist / Taylorist production techniques, to understand the process of flexibility of labor relations as currently at present. In this context, outsourcing is particularly important for portraying one of the ways that best portrays the world of flexible working, with all the implications inherent to them, especially the weakening of workers' rights. To do this we chose the construction segment to accomplish our study, because it is a strongly marked by sector manpower outsourcing, and bring complexities inherent in the activity. From the empirical research conducted on construction sites of two construction of Araraquara / SP, we see many faces of outsourcing, which makes it even more complex the topic at hand and encourages research in this area

As transformações no universo do trabalho vêm afetando de modo intenso às sociedades industriais de todo o mundo, de modo que o processo de reestruturação das atividades produtivas inclui inovações tecnológicas e novas formas de gestão da força de trabalho, o que resulta num aumento significativo nos índices de produtividade, profundas alterações no relacionamento entre as empresas e nas formas de organização da produção, interferindo nas relações de trabalho e no processo de negociação com as instituições de defesa dos trabalhadores. Este trabalho analisa a flexibilização das relações de trabalho, consubstanciado no processo de terceirização da mão de obra no segmento econômico da construção civil em Araraquara/SP. Para tanto, propomos uma análise inicial sobre as técnicas de produção fordista/taylorista, para compreendermos o processo de flexibilização das relações de trabalho tal como se apresenta atualmente. Neste contexto, a terceirização assume especial relevância por retratar uma das formas que melhor demonstra o mundo do trabalho flexível, com todas as implicações que lhes são inerentes, sobretudo o enfraquecimento dos direitos dos trabalhadores. Escolhemos o segmento da construção civil para realizarmos o nosso estudo, por tratar-se de um setor fortemente marcado pela terceirização de mão de obra, além de trazer consigo complexidades inerentes à própria atividade. A partir da pesquisa empírica realizada em canteiros de obras de duas construtoras de Araraquara/SP, constatamos várias faces da terceirização, o que torna ainda mais complexo o tema em questão e fomenta pesquisas nesta área
Keywords: Trabalho; Construção civil - Aspectos sociais; Terceirização; Produtividade; Contracting out